2016
DOI: 10.1007/s10956-016-9654-0
|View full text |Cite
|
Sign up to set email alerts
|

STEM Pathways: Examining Persistence in Rigorous Math and Science Course Taking

Abstract: From 2006 to 2012, Florida Statute §1003.4156 required middle school students to complete electronic personal education planners (ePEPs) before promotion to ninth grade. The ePEP helped them identify programs of study and required high school coursework to accomplish their postsecondary education and career goals. During the same period Florida required completion of the ePEP, Florida's Career and Professional Education Act stimulated a rapid increase in the number of statewide high school career academies. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…PSM techniques have been used previously to purge bias from the estimates of the effect of attendance at certain type of school (Kieffer, ; Reardon, Cheadle, & Robinson, ), but rarely (see Gnagey and Lavertu () and Ashford, Lanehart, Kersaint, et al. () for exceptions), to assess the impact of high schools with STEM programs. In this study, we use multilevel PSM to adjust for a number of pretreatment predictors of students’ probability of joining a high school with a math and science–focused program and to conclude if the impact exists or not.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…PSM techniques have been used previously to purge bias from the estimates of the effect of attendance at certain type of school (Kieffer, ; Reardon, Cheadle, & Robinson, ), but rarely (see Gnagey and Lavertu () and Ashford, Lanehart, Kersaint, et al. () for exceptions), to assess the impact of high schools with STEM programs. In this study, we use multilevel PSM to adjust for a number of pretreatment predictors of students’ probability of joining a high school with a math and science–focused program and to conclude if the impact exists or not.…”
Section: Methodsmentioning
confidence: 99%
“…The other schools had negligible or, often, negative effects across both STEM and, particularly, non‐STEM subjects. Ashford, Lanehart, Kersaint, Lee, and Kromrey () using propensity score methods examined the impact of students’ participation in STEM career academies on their persistence in rigorous mathematics and science course‐taking patterns. Their study found that participation in STEM career academies did not support persistence in rigorous mathematics and science courses in either Florida or national samples of high school students.…”
Section: Prior Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, they developed foreign language, science, and mathematics course‐taking pipeline classifications. Other studies in STEM education have used these classification schemes (Ashford, Lanehart, Kersaint, Lee, & Kromrey, ; Tyson, Lee, Borman, & Hanson, ). We focused on the highest rigor of STEM courses offered on‐site at the schools.…”
Section: Methodsmentioning
confidence: 99%